1987
DOI: 10.1121/1.394512
|View full text |Cite
|
Sign up to set email alerts
|

Intelligibility of average talkers in typical listening environments

Abstract: Intelligibility of conversationally produced speech for normal hearing listeners was studied for three male and three female talkers. Four typical listening environments were used. These simulated a quiet living room, a classroom, and social events in two settings with different reverberation characteristics. For each talker, overall intelligibility and intelligibility for vowels, consonant voicing, consonant continuance, and consonant place were quantified using the speech pattern contrast (SPAC) test. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…While several researchers (e.g. Cox et al, 1987;Jones et al, 2007) have demonstrated that slower speaking rates lead to increased speech intelligibility in noise, Sommers (1997) failed to find a perceptual correlate of speaking rate for young listeners with normal hearing. In addition, Bond and Moore (1994) and Hazan and Markham (2004) observed that words with longer duration led to an increased intelligibility in the presence of noise while no such effect of word duration was found in Uchanski et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…While several researchers (e.g. Cox et al, 1987;Jones et al, 2007) have demonstrated that slower speaking rates lead to increased speech intelligibility in noise, Sommers (1997) failed to find a perceptual correlate of speaking rate for young listeners with normal hearing. In addition, Bond and Moore (1994) and Hazan and Markham (2004) observed that words with longer duration led to an increased intelligibility in the presence of noise while no such effect of word duration was found in Uchanski et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…spectrum measured by Cox, Alexander, and Gilmore (1987a), which was not derived from any of the passages in the CST.…”
Section: Hearing Loss Desensitizationmentioning
confidence: 99%
“…Instead, a variety of research findings suggest that speech intelligibility is also influenced by properties of the listener ͑e.g., Bent and Bradlow, 2003;Imai et al, 2003;Labov and Ash, 1997;Mason, 1946͒ and linguistic context ͑e.g., Healy and Montgomery, 2007͒, as well as interactions among these factors ͑e.g., Moore, 2003;Rogers et al, 2006͒. Whether differences across talkers are maintained under different listening environments is an issue that has not been extensively studied. In one of the few extant studies, Cox et al ͑1987͒ found that relative intelligibility rankings among six talkers were generally maintained across four levels of noise degradation ͑speech mixed with babble͒. More recently, Green et al, ͑2007͒ reported no differences in talker intelligibility among three groups of listeners: normalhearing listeners, CI listeners, and simulated CI listeners.…”
Section: A Speech Intelligibilitymentioning
confidence: 99%